2017
DOI: 10.3390/ijerph14010076
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Design, Physical Activity, and Wellbeing: Applying the Walkability Model

Abstract: Neighborhood design affects lifestyle physical activity, and ultimately human wellbeing. There are, however, a limited number of studies that examine neighborhood design types. In this research, we examine four types of neighborhood designs: traditional development, suburban development, enclosed community, and cluster housing development, and assess their level of walkability and their effects on physical activity and wellbeing. We examine significant associations through a questionnaire (n = 486) distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 64 publications
1
33
1
7
Order By: Relevance
“…Enclosed communities did not obtain the highest means for any well-being benefit. Finally, this article outlined the importance of including vegetation throughout neighborhoods to increase physical activity and well-being [70].…”
Section: Discussionmentioning
confidence: 99%
“…Enclosed communities did not obtain the highest means for any well-being benefit. Finally, this article outlined the importance of including vegetation throughout neighborhoods to increase physical activity and well-being [70].…”
Section: Discussionmentioning
confidence: 99%
“…Surgeon General released a call to action to promote walking and walkable communities. Travel-related decisions are influenced by the neighborhood's level of walkability, or how conducive the built environment is to walking [13,14]. Research has found that perceived neighborhood walkability is positively associated with being physically active [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Informed by the SIA and HBA literatures and in considering the other literatures presented within this paper (Zuniga-Teran et al 2017;Wutich et al 2017;Sinnett et al 2017;Karami et al 2017;Winz, Trowsdale, and Brierley 2014;Alcock et al 2014;Esteves, Franks, and Vanclay 2012;Tzoulas et al 2007), the authors have crafted a set of existing and potential future inclusivity and appropriateness indicators in Table 2. Existing indicators are those that are already incorporated, future ones are those that could be added subject to development with appropriate participatory processes and that consider the many properties of resilience (using the widest definition represented across the literatures examined herein).…”
Section: Embedding Social Appropriateness and Inclusivity In Engineermentioning
confidence: 99%
“…Whilst still engineered, green infrastructure (GI; categorised in Hoang and Fenner 2016;Vogel et al 2015) and nature-based solutions (NBS) (and other such terms, including those outlined in Fletcher et al 2015), are inherently less centralised approaches to infrastructure provision. These approaches can offer multiobjective delivery of services that meet the needs of everyday social practices or water-using microcomponents of demand, as well as bringing additional health and well-being benefits (Zuniga-Teran et al 2017;White et al 2016;Alcock et al 2014;Browne et al 2014;Tzoulas et al 2007). Yet their decentralised character presents a challenge, where ownership and agency may be distributed amongst a range of organisations and communities (Ward and Butler 2016;Hoang and Fenner 2016;Winz, Brierley, and Trowsdale 2011;Winz, Trowsdale, and Brierley 2014).…”
Section: Introductionmentioning
confidence: 99%